1972
DOI: 10.1172/jci106779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fasting and Feeding on Protein Synthesis by the Rat Pancreas

Abstract: A B S T R A C T These experiments were designed to determine whether fasting and feeding were associated with differing rates of protein synthesis in the rat pancreas. It has been established that feeding, acetylcholine, or cholecystokinin-pancreozymin administration was associated with enhanced rates of digestive enzyme secretion; however, the literature is unclear as to effects of such stimulation on enzyme synthesis. Rats fed ad lib. or fasted 24, 48, or 72 hr were used for this study. Pancreases were remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

1973
1973
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…Morisset and Webster (23) found that incorporation of [I4C]-phenylalanine at a concentration of 48 pM into protein was linear for at least 120 min in adult pancreas and the rate of incorporation was not dependent on phenylalanine pool size. In contrast Bauduin et al (24,25) found that while incorporation of L-[4,5-3H]-leucine in vitro into rat pancreas was linear for less than 20 min at a concentration of 26 p M leucine, it was linear for 2 h at a concentration of 0.8 mM.…”
Section: Discussionmentioning
confidence: 99%
“…Morisset and Webster (23) found that incorporation of [I4C]-phenylalanine at a concentration of 48 pM into protein was linear for at least 120 min in adult pancreas and the rate of incorporation was not dependent on phenylalanine pool size. In contrast Bauduin et al (24,25) found that while incorporation of L-[4,5-3H]-leucine in vitro into rat pancreas was linear for less than 20 min at a concentration of 26 p M leucine, it was linear for 2 h at a concentration of 0.8 mM.…”
Section: Discussionmentioning
confidence: 99%
“…phénomène discontinu fortement stimulé par l'ingestion d'aliments. Morisset et al [1972] ont clairement montré à partir de cultures de tissu pancréatique de rats que la synthèse est également un processus variable et qu'une augmentation de la sécrétion est fréquem ment associée à une augmentation de la syn thèse. L'existence d'une intense stimulation de la synthèse pancréatique en période post prandiale est confirmée par Girard-Globa [1980].…”
Section: Discussionunclassified
“…In addition, rates of incorporation of [ 3 H]uridine into RNA were lower in pancreatic tissue slices prepared from fasted compared with fed birds (15) . Preliminary experiments (9) suggested that particulate factors concerned with protein synthesis (in vitro) were more affected by fasting than were soluble factors . In the experiments reported here, there were decreases in amounts of polysomal RNA as well as a shift to monosomes and disomes .…”
Section: Discussionmentioning
confidence: 99%
“…(17) was used as reported previously (9) . (21), and either 5 mg ER, 4 mg polysomes, or 2 mg salt-washed ribosomes .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation